Metformin promotes autophagy in Echinococcus granulosus larval stage - Loos, Julia Alexandra (2018)
Cystic echinococcosis is a neglected parasitic disease caused by the larval stage of Echinococcus granulosus for which an effective treatment is not yet available. Since autophagy constitutes a homeostatic mechanism during stress, either inhibition or activation of its activity might be detrimental for survival of the parasite. Amongst the critical molecules that regulate autophagy, TOR, AMPK and sirtuins are the best characterized ones. Previously, we have identified the autophagic machinery, the occurrence of TORC1-controlled events, and the correlation between autophagy and the activation of the unfolded protein response in E. granulosus larval stage. In addition, we have demonstrated that the parasite is susceptible to metformin (Met), a drug that indirectly activates Eg-AMPK and induces energy stress. In this work, we demonstrate that Met induces autophagy in the E. granulosus larval stage. Electron microscopy analysis revealed the presence of autophagic structures in Met-treated protoscoleces. In accordance with these findings, the autophagic marker Eg-Atg8 as well as the transcriptional expression of Eg-atg6, Eg-atg8, Eg-atg12 and Eg-atg16 genes were significantly up-regulated in Met-treated parasites. The induction of the autophagic process was concomitant with Eg-foxO over-expression and its nuclear localization, which could be correlated with the transcriptional regulation of this pathway. On the other hand, the expression of Eg-AKT and Eg-Sirts suggests a possible participation of these conserved proteins in the regulation of Eg-FoxO. Therefore, through pharmacological activation of the AMPK-FoxO signaling pathway, Met could play a role in the death of the parasite contributing to the demonstrated anti-echinococcal effects of this drug. The understanding of the regulatory mechanisms of this pathway in E. granulosus represents a solid basis for choosing appropriate targets for new chemotherapeutic agents.